2019
DOI: 10.1002/ptr.6308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioavailable phenolic compounds from Ilex paraguariensis on the brain of mice with lung adenocarcinoma

Abstract: Lung carcinoma is one of the most common cancers and has a high mortality.Recently, we showed that it produces neurological paraneoplastic syndrome, with Ilex paraguariensis (IP) extract exerting palliative effects due to its content of phenolic compounds. It is possible, therefore, that these diet agents can arrive at the brain and exert neuroprotection, after the oral intake of IP. Here, the aim was to investigate the protective role of bioavailable IP compounds on the telencephalon and diencephalon in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In hypoxia-induced injury of pheochromocytoma (PC-12) cells, quercetin was found to be effective by activating AMPK and Wnt/β-catenin signaling pathways via down-regulation of miR-122 as reported by Yan et al [134]. Quercetin was reported to be found in the brain and other organs, including tumors induced in mice for studying the intake of Ilex paraguariensis A. St.-Hil [135]. They hypothesized that quercetin and chlorogenic acid present in Ilex paraguariensis A. St.-Hil, if taken in diet, can reduce lung cancer-related neuroinflammation.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 90%
“…In hypoxia-induced injury of pheochromocytoma (PC-12) cells, quercetin was found to be effective by activating AMPK and Wnt/β-catenin signaling pathways via down-regulation of miR-122 as reported by Yan et al [134]. Quercetin was reported to be found in the brain and other organs, including tumors induced in mice for studying the intake of Ilex paraguariensis A. St.-Hil [135]. They hypothesized that quercetin and chlorogenic acid present in Ilex paraguariensis A. St.-Hil, if taken in diet, can reduce lung cancer-related neuroinflammation.…”
Section: Quercetin As a Neuroprotective Agentmentioning
confidence: 90%
“…It also has properties to treat dementia. More recently, several groups of researchers have demonstrated that I. paraguariensis derivatives are abundant with bioactive compounds which when enters CNS and produces significant therapeutic indices( Cittadini et al, 2019 ). Leaves aqueous extract of this medicinal herb has been shown to potentially inhibit scopolamine-induced memory loss in male Swiss mice ( Santos et al, 2015 ).…”
Section: List Of Herbs Having Memory and Cognition-enhancing Propertiesmentioning
confidence: 99%
“…In vivo studies show that infusion could inhibit oxidation of LDL (low density lipoprotein), also contributing to treatments of obesity, diabetes, and arteriosclerosis (Godoy et al, 2013;Habtemariam, 2019;Luís et al, 2019). Recent research has shown numerous therapeutic qualities of yerba mate, including hepatoprotective, neuroprotective, resistance against oxidative stress, antiobesity, cardioprotection, and antioxidant effects ( Figure 5) (Baeza et al, 2017;Cahuê et al, 2019;Cittadini et al, 2019b;Panza et al, 2018;Valenca et al, 2019).…”
Section: Chemical Aspects Bioactive Compounds and Their Functionalitiesmentioning
confidence: 99%